Testing treat-to-target outcomes with initial methotrexate monotherapy compared with initial tumour necrosis factor inhibitor (adalimumab) plus methotrexate in early rheumatoid arthritis - Kavanaugh, Arthur (Ann Rheum Dis, 2018)
OBJECTIVES: To compare responses in patients with early rheumatoid arthritis (RA) initially treated with the tumour necrosis factor inhibitor (TNFi) adalimumab+methotrexate (MTX) versus MTX monotherapy who may have continued receiving MTX or switched to adalimumab rescue therapy after inadequate response to MTX. METHODS: OPTIMA enrolled MTX-naive patients with active RA for <1 year. This post hoc analysis determined the proportion of patients, stratified by initial treatment, who achieved 28-joint modified Disease Activity Score based on C reactive protein <3.2, normal function and/or no radiographic progression at weeks 26, 52 and 78. RESULTS: Significantly greater proportions of patients initially treated with adalimumab+MTX (n=466) compared with MTX monotherapy (n=460) achieved good clinical (53% vs 30%), functional (45% vs 33%) and radiographic (87% vs 72%) outcomes at week 26. From weeks 26 to 78, adalimumab rescue patients achieved similar clinical and functional outcomes versus patients initially treated with adalimumab+MTX. However, significantly more patients initially treated with adalimumab+MTX had no radiographic progression at weeks 52 and 78 versus patients initially treated with MTX (both timepoints: 86% vs 72%). CONCLUSIONS: In early RA, starting with MTX monotherapy and adding TNFi after 26 weeks yields similar longer term clinical results as starting with TNFi+MTX combination therapy but allows a small but significant accrual of radiographic damage.